Using scenarios to make decisions about the future: anticipatory learning for the adaptive co-management of community forests - Wollenberg, Eva Karoline; Edmunds, D.; Buck, L. (2000)
Current trends to improve the adaptiveness of community forest management focus on monitoring past actions and emphasise internal dynamics. Scenario methods can be used to: (1) enable managers to better understand landscape and larger scale forces for change and to work with stakeholders at these levels; and (2) improve adaptiveness not only by responding to changes, but also by anticipating them. Methods related to scenario analysis are reviewed and there is discussion on how they can be adapted to community management settings to improve the responsiveness and the collaboration among stakeholders. This review is used to identify the key elements of scenario methods that CIFOR will test among communities in Bulungan Regency, East Kalimantan, Indonesia and two villages in the buffer zone of Ranomafana National Park, Madagascar.